Efektivitas Metode 2S (Swinging, Sushing) terhadap Peningkatan Kualitas Tidur Bayi di PMB Lilis Sugianti Kota Pekanbaru - Hidayati, Nurul; Yahya, Nursiah; Ahid, Okmawati; Aritonang, Nursyaini Hot; Nababan, Tiarnida (Innovative: Journal Of Social Science Research, 2024)
The growth of the baby is affected by the time of rest or sleep. Deep sleep is more important for the growth of the baby, because during sleep the baby's brain grows to reach its center. On the other hand, when sleeping, the baby's body processes hormones, which grow three times larger than when the baby is awake. The 2S (Swinging, Sushing) method is a model used to improve the baby's sleep quality. This research aims to investigate the effectiveness of the 2S (Sushing and Swinging) method on infant sleep quality. This research scheme is based on Crosssectional strategies. Based on the examined research, it was concluded that the effectiveness of the 2S (Sushing And Swinging) Method has been linked to the improvement of the quality of sleep of infants where the Chi-Square ρ-value score (0.05) ranges from 0.035, indicating that the 2S (Sushing And Swinging) model is effective in improving the quality of sleep of infants.